Isolation of Potent CGRP Neutralizing Antibodies Using Four Simple Assays. (January 2016) - Neal, Frances; Arnold, Joanne; Rossant, Christine J.; Podichetty, Sadhana; Lowne, David; Dobson, Claire; Wilkinson, Trevor; Colley, Caroline; Howes, Rob; Vaughan, Tristan J.
Calcitonin gene-related peptide (CGRP) is a small neuropeptide and a potent vasodilator that is widely associated with chronic pain and migraine. An antibody that inhibits CGRP function would be a potential therapeutic for treatment of these disorders. Here we describe the isolation of highly potent antibodies to CGRP from phage and ribosome display libraries and characterization of their epitope, species cross-reactivity, kinetics, and functional activity. Homogenous time-resolved fluorescence (HTRF) binding assays identified antibodies with the desired species cross-reactivity from naïve libraries, and HTRF epitope competition assays were used to characterize and group scFv by epitope. The functional inhibition of CGRP and species cross-reactivity of purified scFv and antibodies were subsequently confirmed using cAMP assays. We show that epitope competition assays could be used as a surrogate for functional cell-based assays during affinity maturation, in combination with scFv off-rate ranking by biolayer interferometry (BLI). This is the first time it has been shown that off-rate ranking can be predictive of functional activity for anti-CGRP antibodies. Here we demonstrate how, by using just four simple assays, diverse panels of antibodies to CGRP can be identified. These assay formats have potential utility in the identification of antibodies to other therapeutic targets.